Penerapan Mixed Integer Programming dalam Pengoptimalan Keuntungan pada D’Laundry Factory Pekanbaru - Elfira Safitri; Sri Basriati; Khotimah Khotimah; Mohammad Soleh; Retno Ayu Puji Lestari; Nilwan Andiraja (Jurnal Sains Matematika dan Statistika, 2023)
D’Laundry Factory is one of the businesses engaged in washing and ironing services. The problem that is often faced by laundry business owner is determining the amount of laundry items received by D’Laundry Factory to optimize maximum profits. The purpose of this study was to determine the combination of the number of laundry items received by the D’Laundry Factory to optimize profits using Mixed Integer Programming. The method used in this research is the Branch and Bound method. Based on the results of the study obtained that the DLaundry Factory Pekanbaru business received blanket 70 kg, bedcover 750 kg, dolls 20 kg, shoes 90 kg, bags 17,5 kg, helmets 30 kg, strollers 511 kg, curtains 200 kg, clothes 325.4 kg with a maximum profit of Rp.15.745.850.